2020
DOI: 10.1007/s00204-020-02938-5
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of myricetin bulk and nano forms in vitro in lymphocytes from myeloma patients

Abstract: Evading apoptosis and chemo-resistance are considered as very important factors which help tumour progression and metastasis. Hence, to overcome chemo-resistance, there is an urgent requirement for emergence of more effective treatment options. Myricetin, a naturally occurring flavonoid, is present in various plant-derived foods and shows antitumour potential in different cancers. In the present in vitro study, results from the comet assay demonstrated that myricetin bulk (10 µM) and nano (20 µM) forms exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, western blot results showed that lymphocytes from myeloma patients had higher p53 protein levels and lower Bcl-2/Bax ratios than did lymphocytes from healthy people. The regulation of apoptotic proteins activated by myricetin exposure in lymphocytes of myeloma patients occurred via P53 as well as oxidative stress-dependent pathways, as evidenced by the notable increase in intracellular reactive oxygen species level [115].…”
Section: Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, western blot results showed that lymphocytes from myeloma patients had higher p53 protein levels and lower Bcl-2/Bax ratios than did lymphocytes from healthy people. The regulation of apoptotic proteins activated by myricetin exposure in lymphocytes of myeloma patients occurred via P53 as well as oxidative stress-dependent pathways, as evidenced by the notable increase in intracellular reactive oxygen species level [115].…”
Section: Myelomamentioning
confidence: 99%
“…Comet assay demonstrated that myricetin bulk (10 µM) and nano (20 µM) forms exhibited a non-significant level of genotoxicity in lymphocytes from multiple myeloma patients when compared to those from healthy individuals. [115] Brain cancer 0, 15, 60 and 120 µM increasing doses of myricetin, led to dose-dependent increase in Bax and Bad levels and a dose-dependent decrease in Bcl-2 and Bcl-xl expression levels [116] 0-150 µM…”
Section: Cancer Type Dosage Findingsmentioning
confidence: 99%
“…Alpha-2,6-Sialyltransferase 5 genes (ST6GALNAC5) and MDA-Mb-231Br cells in concentration-dependent manner and in animal model when treated with 50 mg/kg dose (Ci et al, 2018). In recent study by IL-6, NF-κB, and PCNA (Akhtar et al, 2021;Zhang et al, 2018;Zheng et al, 2017). Jung et al (2017) explored that oral administration of myricetin (50 mg/kg/day) in experimental mice for 21 days found increased aerobic capability via enhancing the distance and running time and mitochondrial functions via activating peroxisome proliferator-activated receptor-gamma coactivator (PGC-1α) and SIRT1.…”
Section: Anticancer Effectmentioning
confidence: 99%
“…Myricetin has been found a significant inhibitor of migration, invasion, and adhesion and could reduce the matrix metalloproteinase (MMP‐2/9) activities and mRNA levels of ST6 N‐Acetylgalactosaminide Alpha‐2,6‐Sialyltransferase 5 genes (ST6GALNAC5) and MDA‐Mb‐231Br cells in concentration‐dependent manner and in animal model when treated with 50 mg/kg dose (Ci et al., 2018 ). In recent study by Zhang and colleagues, myricetin induced the suppression of azoxymethane (AOM)/dextran sodium sulfate (DSS) model of (AOM/DSS)‐induced colitis and colorectal tumorigenesis, reduction of size of colorectal polyps, and inflammatory factors IL‐1β, TNF‐α, p‐NF‐κB, IL‐6, NF‐κB, and PCNA (Akhtar et al., 2021 ; Zhang et al., 2018 ; Zheng et al., 2017 ).…”
Section: Health Propertiesmentioning
confidence: 99%
“…Akhtar et al [243] showed that bulk and nano forms of myrcetin showed an insignificant genotoxicity level in the lymphocytes of MM patients compared to those of healthy ones. This effect was induced by altering the Bcl-2 expressions.…”
Section: Myricetinmentioning
confidence: 99%